2022
DOI: 10.1108/ijoem-09-2020-1137
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment inflows and energy diversification in emerging seven economies: evidence from a panel data analysis

Abstract: PurposeHigher economic growth accompanied by rising energy demand poses severe challenges to the long-term environmental sustainability of E7 economies, including Brazil, China, India, Indonesia, Mexico, Russia and Turkey. Thus, this paper explores the influence of foreign direct investment (FDI) inflows on energy diversification for E7 economies.Design/methodology/approachThe dataset is panel data for emerging seven (E7) economies, covering the period 1992–2017. The empirical investigation relies on econometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Recent research has identified probable causes of environmental deterioration and proposed various countermeasures to reduce emissions, specifically consumption-based carbon emissions (CBCO 2 ). For instance, energy consumption has been identified as the primary driver of environmental deterioration [ 9 , 10 ], urbanization [ 11 ], foreign direct investment [ 12 ], financial development and innovation [ 13 , 14 ]. Carbon dioxide emissions have increased unprecedentedly in recent years and are now considered 50 % higher than at the start of the great industrial revolution [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified probable causes of environmental deterioration and proposed various countermeasures to reduce emissions, specifically consumption-based carbon emissions (CBCO 2 ). For instance, energy consumption has been identified as the primary driver of environmental deterioration [ 9 , 10 ], urbanization [ 11 ], foreign direct investment [ 12 ], financial development and innovation [ 13 , 14 ]. Carbon dioxide emissions have increased unprecedentedly in recent years and are now considered 50 % higher than at the start of the great industrial revolution [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, energy–growth nexus and its economic consequences and implications is widely studied (see, e.g. Irfan and Ojha, 2022; Carmona et al. , 2017; Tiba and Omri, 2017; Bruns et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, energy-growth nexus and its economic consequences and implications is widely studied (see, e.g. Irfan and Ojha, 2022;Carmona et al, 2017;Tiba and Omri, 2017;Bruns et al, 2014;Omri, 2014;Ozturk, 2010) but examining energy-growth nexus without considering the role of informal sector can cause misleading results as the underground economy represents large share of GDP, especially in emerging economies (Hassan and Schneider, 2016). Since the two-third of income earned in the underground economy is usually spent in the formal economy (Williams and Schneider, 2016;Schneider and Enste, 2000), it is reasonable to expect that a significant portion of informal income is spent on energy consumption.…”
mentioning
confidence: 99%